2021
DOI: 10.3390/nu13082598
|View full text |Cite
|
Sign up to set email alerts
|

Individual Behavioral Reactions in the Context of Food Sensitivities in Children with Attention-Deficit/Hyperactivity Disorder before and after an Oligoantigenic Diet

Abstract: The influence of food intake on behavior problems of children with Attention-Deficit/Hyperactivity Disorder (ADHD) was already described in the early 20th century. Eliminating food components by using the Oligoantigenic Diet (OD) leads to reduction of ADHD symptoms for more than two-thirds of patients. The aim of our study was to reveal how to identify foods having an impact on ADHD symptomatology. Therefore, 28 children with ADHD participating in this uncontrolled, open trial were examined before and after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…In our open uncontrolled study, Yorgidis et al could replicate and confirm previous results of the efficacy of the OD on children with ADHD in a pre-post design [ 42 , 43 ]. The participants showed individual food sensitivity concerning the type of food, intensity, or pattern of reactivity.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our open uncontrolled study, Yorgidis et al could replicate and confirm previous results of the efficacy of the OD on children with ADHD in a pre-post design [ 42 , 43 ]. The participants showed individual food sensitivity concerning the type of food, intensity, or pattern of reactivity.…”
Section: Introductionsupporting
confidence: 86%
“…For all of those, intolerant food items could be identified. In our previous study, significant improvement was observed in all scales of the ADHD rating scale as the primary outcome measure [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…An open trial conducted by Yorgidis and colleagues explored the role of oligoantigenic diet (OD) as a therapeutic tool within ADHD children [10] and observed that the combination of this diet and the subsequent food challenge was efficient to identify individual food sensitivity in connection with ADHD. OD is an individualized type of elimination diet aimed at identifying specific foods that worsen psychopathological symptoms, followed by reintroducing other alternative foods that improve neuropsychological performance.…”
Section: Diet Intervention On Adhdmentioning
confidence: 99%
“…The current consensus is that none of these factors is either a necessary or sufficient cause, although specific risk factors, such as rare genetic variants and environmental factors, can have a major impact [ 4 ]. Research has shown that nutrition can be an environmental risk factor of major impact in (a subgroup of) children with ADHD: double-blind placebo-controlled research, randomised controlled trials (RCTs) and open trials investigating the effect of a few-foods diet (FFD) on ADHD have shown that ADHD symptoms may significantly decrease after following a 5-week FFD [ 9 , 10 , 11 , 12 , 13 , 14 ]. These results suggest that children with ADHD who show clinically relevant behavioural improvements—i.e., a symptom decrease of at least 40% on the ADHD Rating Scale (ARS)—after following an FFD, can be diagnosed with food-induced ADHD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%